Pengaruh Lama Fermentasi dan Kombinasi Biofertilizer Kotoran Kambing dengan AB Mix terhadap Pertumbuhan Kangkung (Ipomoea reptans Poir.) dalam sistem Hidroponik - Nurhayani H. Muhiddin; Akhmad Syakur; putri damayanti; Sahrani U (Universitas Cokroaminoto Palopo, 2026)
Water spinach (Ipomoea reptans Poir.) is a leafy vegetable that is highly nutritious and has the potential to be cultivated using a hydroponic system with environmentally friendly organic fertilizers. This study aims to determine the effect of fermentation duration and the combination of goat manure biofertilizer with AB Mix on the growth of water spinach (Ipomoea reptans Poir.) in a hydroponic system. The biofertilizer was fermented for 7, 14, and 21 days, then applied to various treatment combinations. The results showed that 7-day fermentation produced the best results in the P125AB75 treatment, with an average leaf width of 1.60 ± 0.56 cm and leaf length of 5.37 ± 1.05 cm. Fourteen-day fermentation produced optimal growth in the P20AB100 treatment with a leaf width of 2.13 ± 0.15 cm and a leaf length of 5.35 ± 0.59 cm. Meanwhile, 21 days of fermentation showed the most significant results in the P30AB100 treatment with a leaf width of 2.30 ± 0.10 cm and a leaf length of 6.45 ± 0.46 cm. Increasing the fermentation period was proven to improve nutrient availability, enrich active metabolites, and stabilize organic compounds, thereby supporting more optimal vegetative growth of water spinach compared to pure manure. Thus, liquid biofertilizer from 21-day fermentation, especially in the P30AB100 combination, is the best treatment for enhancing water spinach growth in hydroponic systems.